Responsibility and Legal Protection for Elderly Notaries for Authentic Deeds They Make - Nurrachman, R. Ali (Jurnal Konstatering, 2025)
A notary is a public official who has the authority to make authentic deeds that have the force of legal evidence.The problems in this thesis are 1)What are the responsibilities of a notary who has retired for the authentic deeds he has made? 2) What is the form of legal protection for a notary after retirement for the authentic deeds he has made?The aim of this research is to find out and analyze the legal responsibilities and protection for notaries.When a notary has entered retirement, the issue arises regarding the continuation of legal responsibility for the deeds that have been made, and the extent to which legal protection still applies to him. This study aims to analyze the form of legal responsibility of a notary public for authentic deeds that they have made and how legal protection is provided after the term of office ends. Method used in the researchThis is a sociological legal approach with a descriptive qualitative method. The results of the study indicate that even though the notary's term of office has ended, the responsibility for the deeds made remains attached to him according to the provisions of Article 65 of the UUJN. However, legal protection for retired notaries is not as strong as when they were still active, resulting in a vacuum of norms and potential legal uncertainty. Therefore, a more stringent legal regulation is needed regarding the limits of responsibility and legal protection for notaries after retirement so that legal certainty and justice can be realized.